Identification and functional characteristics of IL-8 and its potential receptor CXCR1/2 in Siberian hybrid sturgeon - Shiyong Yang; Rong Wei; Xinrui Lyu; Yujie Lv; Yang Xiao; Jiayun Wu; Xiaogang Du; Yunkun Li (Comparative Immunology Reports)
IL-8, also known as CXCL8, was the first chemokine identified in mammals, playing a crucial role in regulating inflammatory responses and immune cell chemotaxis. In fish, IL-8 exhibits a more diverse and complex function that makes it being perplexing. This research focused on cloning the coding sequences (CDS) of IL-8 gene and its potential receptor genes (named CXCR1-1, CXCR1-2, CXCR2-1, and CXCR2-2) from Siberian hybrid sturgeon (Acipenser baerii♀×Acipenser schrenckii♂). Their molecular features, tissue distribution and immune function were analyzed. The CDS length of IL-8 and the receptor genes was 288 bp, 1,135 bp, 1,135 bp, 1,061 bp, and 1,078 bp, respectively. Multiple sequence alignment and phylogenetic analysis showed the relative conservation of their amino acids compared to other fish species. IL-8 and the receptors were broadly expressed in various tissues. Upon infection with Aeromonas hydrophila (A. hydrophila) or Staphylococcus aureus (S. aureus), the expression levels of IL-8 and CXCR2-1/2 were increased in the spleen and head kidney, with a strong expression correlation observed between IL-8 and CXCR2-1/CXCR2-2 in the spleen. Furthermore, recombinant IL-8 demonstrated concentration-dependent chemotactic activity for granulocytes. This study offers valuable insights into the potential signaling pathways and functions of IL-8, thereby contributing to the future in-depth investigation of IL-8-mediated signaling activation in cartilaginous fishes.